Design and Implementation of Automatic GSM Based Fire Alarm System. - Waiswa, Abudallah Mujaasi (Kabale University, 2023)
Fire accident is unplanned and undesirable event that brings damages to social wealth and human life which needs to be prevented at all cost. In order to prevent losses incurred from fire accidents, various alarm systems have been developed such as smoke detectors, temperature sensor based systems etc. With the advancement of technology more automated fire gadgets are now available among which is this design. [l]The availability of GSM technology is now incorporated into the fire alarm system in order to combat and prevent the menace that could be caused by fire accident. This paper presents the design and implementation of a cost effective and reliable automated GSM based fire alarm system. The device will be able to monitor the temperature of the environment, the smoke level, make a call alert to an inbuilt GSM number when necessary, and make loud sound to alert occupants on pending danger. This was achieved by the fabrication of 12 V power supply system that powers the device using step down transformer, programming Arduino Uno Microcontroller using C++ programming Language in the Arduino software platform, and integrating the program med Arduino Uno Microcontroller with GSM SIM900 module. Keywords - Fire Alarm System, Fire-Detector, GSM Network, Arduino Uno Microcontroller [2]